Energy Harvesting from Human Biomechanical Energy for Health-monitoring Devices. Issue 1 (2nd January 2021) - Chaudhary, Parul; Azad, Puneet
ABSTRACT: Conversion of human biomechanical energy into electrical form leads to the development of triboelectric nano-generator (TENG) for the operation of low-power health-monitoring devices. Here, we report a self-powered energy conversion system for sustainable operation of health-monitoring devices consisting of a TENG, an ac–dc converter, and a buck converter. The portable TENG comprising films of polytetrafluoroethylene, Mylar, and aluminium converts rotational motion into useful electricity. We have demonstrated the use of TENG as a power source for health-monitoring devices such as pulse rate monitor and thermometer. It is also capable of measuring the speed of cycling using an odometer and moisture content in the atmosphere using a hygrometer. The maximum energy is found to be 1269 µJ/cm 3 across a 1000 µf capacitor. Also, the maximum power across a 2 MΩ resistor is 240 µW. Such portable systems can act as a power source by harvesting human biomechanical energy while cycling for low-power electronics useful for medical diagnostics and fitness monitoring.